2013
DOI: 10.1002/ggge.20233
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chemical pretreatment of sediment upon foraminiferal‐based proxies

Abstract: [1] Paleoceanographic studies routinely combine different foraminiferal proxies (i.e., weight, abundance, trace metal, and stable isotope measurements) into a cohesive narrative. The application of chemical treatment to disaggregate ocean sediments in the most efficient way to isolate the fossils of foraminifera from the other sediment components is dictated by the time available and the material used. Yet few studies have aimed to test both the physical and geochemical effects associated with such practices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 103 publications
1
18
0
Order By: Relevance
“…As with any foraminifera-based work, sediment disaggregation and sieving is required; detergents and disaggregation agents (Feldmeijer et al 2013) may have high levels of boron and should be avoided.…”
Section: Sample Size and Preparationmentioning
confidence: 99%
“…As with any foraminifera-based work, sediment disaggregation and sieving is required; detergents and disaggregation agents (Feldmeijer et al 2013) may have high levels of boron and should be avoided.…”
Section: Sample Size and Preparationmentioning
confidence: 99%
“…One of the main complications of the biogenic carbonate pretreatment debate is the lack of a consistent standard practice 20,60 . There are inconsistencies in the concentrations of chemical used, in the temperatures used, and in the duration of exposure time (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of biogenic carbonates for O and C isotope analysis using conventional acid digestion followed by mass spectrometry is aimed at preventing the reaction between any organic matter and H 3 PO 4 (phosphoric acid) used to liberate CO 2 from the skeletal carbonate 20,21 . Organics also tend to inhibit complete dissolution of the carbonate material during isotopic analysis 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Effects of chemical oxidation, usually conducted using H 2 O 2, on MgCO 3 have been somewhat more investigated. Both Marr et al (2013) and Feldmeijer et al (2013) found no difference in Mg/Ca for Foraminifera treated with short periods of chemical oxidation. Barker et al (2003) however, saw reductions of up to 25% in Mg/Ca resulting from chemical cleaning, although specimens subjected to less than 20 minutes of oxidative treatment were observed to display an elevated Mg/Ca.…”
Section: Effects Of Bleaching On Compositionmentioning
confidence: 91%